Penerapan Pertanggungjawaban Pidana Terhadap Pelaku Inses AnakKandung - Muhammad Yusril Irza (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2023)
Incest is a form of sexual deviation that often occurs in social life, especially in the family. The factors thatcause incest do not stand alone or single, but are an accumulation of various psychological, socialproblems, mental attitudes, morality and patriarchal culture of the perpetrator. This crime of incest is animmoral and immoral act that threatens children who are victims of sexual intercourse by their ownfamilies. Incest is very rampant in society because it is rarely reported due to the embarrassment for familymembers if it is known by others. The most common perpetrators of sexual violence, including incest, arefathers and uncles. This is sad, because many perpetrators of violence in the personal realm are consideredand expected to be protectors such as fathers, uncles or husbands. Criminal liability for perpetrators ofincest can be charged under Article 287 of the Criminal Code or Article 419 of Law No. 1 of 2023.Meanwhile, for the formulation of acts of incest against children, they can be charged using Article 294paragraph (1) of the Criminal Code or Article 418 paragraph (1) of the Criminal Code. Law No.1 of 2023.Obstacles in accessing justice and recovery also occur when victims do not receive support from theirfamilies, which encourages victims to leave their homes and lose their rights to education and protectionfrom their families.